Intestinal Metabolites Are Profoundly Altered in the Context of HLA–B27 Expression and Functionally Modulate Disease in a Rat Model of Spondyloarthritis. Issue 10 (31st August 2017) - Asquith, Mark; Davin, Sean; Stauffer, Patrick; Michell, Claire; Janowitz, Cathleen; Lin, Phoebe; Ensign‐Lewis, Joe; Kinchen, Jason M.; Koop, Dennis R.; Rosenbaum, James T.
Abstract : Objective: HLA–B27–associated spondyloarthritides are associated with an altered intestinal microbiota and bowel inflammation. We undertook this study to identify HLA–B27–dependent changes in both host and microbial metabolites in the HLA–B27/β2 ‐microglobulin (β2 m)–transgenic rat and to determine whether microbiota‐derived metabolites could impact disease in this major model of spondyloarthritis. Methods: Cecal contents were collected from Fischer 344 33–3 HLA–B27/β2 m–transgenic rats and wild‐type controls at 6 weeks (before disease) and 16 weeks (with active bowel inflammation). Metabolomic profiling was performed by high‐throughput gas and liquid chromatography–based mass spectrometry. HLA–B27/β2 m–transgenic rats were treated with the microbial metabolites propionate or butyrate in drinking water for 10 weeks, and disease activity was subsequently assessed. Results: Our screen identified 582 metabolites, of which more than half were significantly altered by HLA–B27 expression at 16 weeks. Both microbial and host metabolites were altered, with multiple pathways affected, including those for amino acid, carbohydrate, xenobiotic, and medium‐chain fatty acid metabolism. Differences were even observed at 6 weeks, with up‐regulation of histidine, tyrosine, spermidine, N ‐acetylmuramate, and glycerate in HLA–B27/β2 m–transgenic rats. Administration of the short‐chain fatty acid propionate significantly attenuated HLA–B27–associated inflammatory disease, although this was not associated with increased FoxP3+ T cell induction or with altered expression of the immunomodulatory cytokines interleukin‐10 (IL‐10) or IL‐33 or of the tight junction protein zonula occludens 1. HLA–B27 expression was also associated with altered host expression of messenger RNA for the microbial metabolite receptors free fatty acid receptor 2 (FFAR2), FFAR3, and niacin receptor 1. Conclusion: HLA–B27 expression profoundly impacts the intestinal metabolome, with changes evident in rats even at age 6 weeks. Critically, we demonstrate that a microbial metabolite, propionate, attenuates development of HLA–B27–associated inflammatory disease. These and other microbiota‐derived bioactive mediators may provide novel treatment modalities in HLA–B27–associated spondyloarthritides.